1981
DOI: 10.1007/bf01440913
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the tensor force effects on the spin-orbit splitting in spherical and very deformed nuclei

Abstract: A contribution of the tensor force to the phenomenological spin-orbit (SO) potential in the single-particle Hamiltonian is studied for spherical and deformed rare-earth and actinide nuclei. It is found that the deformation dependence of the SO coupling constant, suggested by the second order tensor force contribution, enables to explain the observed single particle (s.p.) states in the second minimum of 237pu and 239pu using a SO strength weaker than usually applied. Consequences of the tensor contributions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The selection rules for the matrix elements of VLS are the same as for the first order LS-potentials and are given in [ 6 ] .…”
Section: The Generalized Spin-orbit Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection rules for the matrix elements of VLS are the same as for the first order LS-potentials and are given in [ 6 ] .…”
Section: The Generalized Spin-orbit Potentialmentioning
confidence: 99%
“…Consequently, radii of the effective SO potential and the tensor potential differ. In [6] we have shown that the main effect of the tensor force contribution in the spherical WS potential is to raise the energy of intruder states. This leads, e.g., to specific changes of shell effects at large angular momenta or large deformations.…”
Section: Introductionmentioning
confidence: 97%